Bunyaviral Cap-Snatching Endonuclease Activity and Inhibition with Baloxavir-like Inhibitors in the Context of Full-Length L Proteins - Arlo J. Loutan; Baiuyan Yang; Gabrielle Connolly; Adam Montoya; Robert J. Smiley; Arnab K. Chatterjee; Matthias Götte (Viruses)
The Bunyavirales order includes a range of zoonotic viruses, which can cause severe disease in humans. The viral replication machinery is a logical target for the development of direct-acting antivirals. Inhibition of the cap-snatching endonuclease activity of related influenza viruses provides a proof of concept. Using the influenza B virus (IBV) RNA-dependent RNA polymerase complex as a benchmark, we conducted a comparative analysis of endonuclease activities of recombinant full-length bunyaviral L proteins using gel-based assays. The IBV complex demonstrates specific endonucleolytic cleavage and a clear preference for capped substrates. In contrast, severe fever with thrombocytopenia syndrome, Sin Nombre, and Hantaan virus L proteins readily cleave capped and uncapped RNAs to a broader spectrum of RNA fragments. Active site mutants further help to control for the potential of contaminating nucleases, exonuclease activity, and RNA hydrolysis. The influenza cap-snatching inhibitor baloxavir and derivatives have been used to validate this approach. In conclusion, the results of this study demonstrate the importance of assays with single nucleotide resolution and the use of full-length L proteins as a valuable experimental tool to identify selective endonuclease inhibitors.